PKM Pelatihan Pemanfaatan Literasi Digital Berbasis Android untuk Meningkatkan Hasil Belajar Siswa di SMP Negeri 4 Bajeng - Ninik Rahayu Ashadi; Suwahyu, Irwansyah; Muhammad Asriadi; Dwi Rezky Anandari Sulaiman; Shabrina Syntha Dewi (Sakura Digital Nusantara, 2023)
This PKM is about PKM training on the use of Android-based digital literacy to improve student learning outcomes at SMPN 4 Bajeng. The problems faced by these partners are lack of understanding of students regarding the use of Android-based digital literacy, lack of motivation to do assignments which results in poor learning outcomes, students have cellphones and laptops but they are only used as communication tools and tools for typing assignments. Based on this It seems necessary to equip students with knowledge of the use of digital literacy. The solution offered by the service team is to conduct training on the use of digital literacy. In implementing this PKM program, class X students will be invited who will later by following this training become students who are able to utilize digital literacy in the learning process. This training will present presenters who are competent in their fields. The speakers presented were from educational circles, both lecturers and teachers who are capable of developing their profession, especially the use of digital literacy: (1) Welcoming the service team from Makassar State University by the principal of SMP 4 Bajeng, (2) Activities providing materials, (3) Mentoring and evaluation of class X students at SMP 4 Bajeng. Training methods are lecture methods, question and answer methods, and training/practice methods.